2000
DOI: 10.1021/ja994040i
|View full text |Cite
|
Sign up to set email alerts
|

Individual Supramolecular Host−Guest Interactions Studied by Dynamic Single Molecule Force Spectroscopy

Abstract: Supramolecular host-guest interactions in aqueous environment were studied by dynamic single molecule force spectroscopy. The unbinding between ferrocene moieties immobilized on atomic force microscopy tips and -cyclodextrin receptors in highly ordered self-assembled monolayers on Au(111) was studied. The rupture force of individual ferrocene--cyclodextrin complexes was found to be 56 ( 10 pN. The value of this unbinding force was independent of the unloading rate. This was attributed to the fast (de)complexat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(165 citation statements)
references
References 25 publications
7
157
0
1
Order By: Relevance
“…48. The dependence of the bond-rupture force on the loading/unloading rate has been studied in a number of works [673,1132,1133]. Lo et al [1134] have studied this dependence with biotin-streptavidin, taking advantage of the Poisson statistic method illustrated in Section 5, and have shown that the bond strength depends linearly on the logarithm of the loading rate (see Eq.…”
Section: Rupture Force Of Specific Interactionsmentioning
confidence: 99%
“…48. The dependence of the bond-rupture force on the loading/unloading rate has been studied in a number of works [673,1132,1133]. Lo et al [1134] have studied this dependence with biotin-streptavidin, taking advantage of the Poisson statistic method illustrated in Section 5, and have shown that the bond strength depends linearly on the logarithm of the loading rate (see Eq.…”
Section: Rupture Force Of Specific Interactionsmentioning
confidence: 99%
“…Histograms were prepared by using OriginPro (OriginLab). Peaks were fitted by using autocorrelation analysis (45) or a Lorentzian function (see SI Text for further discussion). Each histogram was the result of at least 100 separate force measurements.…”
Section: Materials Oligonucleotidesmentioning
confidence: 99%
“…20,23,[28][29][30][31][32][33][34][35]37,38 We have evaluated the single force for specific hydrogen bonding between the phenylurea and carboxyl groups by a statistical method using autocorrelation analysis of the values of the adhesion force. In this analysis, an autocorrelation function is computed for the histogram data of the observed pull-off forces.…”
Section: Single Force Of Hydrogen Bonding On Mixed Mha/ht Sams (Cooh/mentioning
confidence: 99%
“…In this analysis, an autocorrelation function is computed for the histogram data of the observed pull-off forces. 20,31 Then, the single force can be evaluated from the period of the calculated autocorrelation function. Figure 5 gives examples of the autocorrelation functions for repetitive measurements of the adhesion forces between the PhUET-tip and MHA/HT binary mixed SAMs prepared by the SAM coating solution at MHA mole fractions of 0.3 and 0.8.…”
Section: Single Force Of Hydrogen Bonding On Mixed Mha/ht Sams (Cooh/mentioning
confidence: 99%
See 1 more Smart Citation